The effect of deacetylation degree of konjac glucomannan on microbial metabolites and gut microbiota in vitro fermentation. (March 2020) - Ouyang, Dongmei; Deng, Jie; Zhou, Kai; Liang, Yuxuan; Chen, Yongchun; Wang, Da; Zhong, Jing; Sun, Yuanming; Li, Meiying
Graphical abstract: Highlights: Low and medium deacetylation degree have little effect on the fermentability of KGM. High deacetylation degree showed lower fermentability than that of KGM. The lower fermentability be related to the change of physicochemical properties. The deacetylation degree should be considered in the production of konjac foods. Abstract: Deacetylation was a phenomenon widely existed during konjac glucomannan (KGM) processing, which highly effected its functional properties. Herein, influence of deacetylation degree (DD) of KGM on microbial metabolites and gut microbiota was studied in vitro . The fermentability of KGM was relatively stable under the low (Da1) and medium (Da2) DD. But high DD (Da3) shown lower fermentability than that in KGM, which was characterized with the decreasing reducing sugar content, endo -β-mannanase activity and total short-chain fatty acids (SCFAs). Meanwhile, compared with KGM, Da3 shown lower relative abundance of Actinobacteria and Bacteroide, and higher amounts of Fusobacteria and Proteobacteria to some extent. The negative effect on fermentability caused by deacetylation might be related to the reduction of solubility and viscosity, and increase the degree of molecular ordering. Our findings suggested that control of DD should be taken into consideration in the process of making konjac gel products.